Pacey Packer, unicorn tracker. 2, Horn slayer - Phillipps, J. C. (Julie C.) (New York : Random House, 2021)
After slicing the horn off of the Evil Apha Unicorn and becoming a legend, Pacey Packer returns to Rundalyn to free the statue children she left behind.
Kirkus Review, April 2021
4.0
3-6
GN230L
Keywords: Toys -- Comic books, strips, etc -- Juvenile fiction; Unicorns -- Comic books, strips, etc -- Juvenile fiction; Sisters -- Comic books, strips, etc -- Juvenile fiction; Fantasy comic books, strips, etc; Adventure stories; Toys -- Fiction; Unicorns -- Fiction; Sisters -- Fiction; Fantasy; Adventure and adventurers -- Fiction; Cartoons and comics; Fantasy comics; Action and adventure comics; Graphic novels; Comics (Graphic works)